Implementation of Warehouse Inventory Management System at CV Cahaya Karunia Mulia - Hermawan, Muhamad Taufik; Hasan, Fuad Nur; Kuntoro, Antonius Yadi (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The development of information technology has driven efficiency in various aspects of company operations, including inventory management. CV Cahaya Karunia Mulia, a company engaged in marble distribution, still uses Google Spreadsheets as the main tool for warehouse inventory management. This condition creates the risk of data discrepancies and hinders operational efficiency. This research aims to analyze requirements, design, implement, and test a web-based warehouse inventory management system for the company. The method used is the Waterfall approach, consisting of requirement analysis, system design, implementation, testing, as well as deployment and maintenance. The results show that the developed system is able to meet the company’s functional and non-functional requirements, with key features such as master data management, inventory transactions, and stock monitoring. System testing indicates that all functions run as expected and are capable of improving efficiency, accuracy, and effectiveness in warehouse inventory management. Therefore, this system can serve as a solution that significantly supports smooth operational processes.